Synopsis of Lasioglossum (Dialictus) Robertson, 1902 (Hymenoptera, Apoidea, Halictidae) in Japan, the Korean Peninsula and Taiwan - Ryuki Murao; Osamu Tadauchi; Heung-Sik Lee (European Journal of Taxonomy, 2015)
Twelve species in total are recognized for the subgenus Lasioglossum (Dialictus) Robertson, 1902 from Japan, the Korean Peninsula and Taiwan. Lasioglossum (Dialictus) alishanense sp. nov. and L. (D.) taiwanense sp. nov. from Taiwan, are described as new. Four species are recorded from the following localities for the first time: L. (D.) miyabei Murao, Ebmer & Tadauchi, 2006 from the Korean Peninsula (South Korea); L. (D.) ellipticeps (Blüthgen, 1923), L. (D.) virideglaucum Ebmer & Sakagami, 1994 and L. (D.) viridellum (Cockerell, 1931) from South Korea. Lasioglossum (Dialictus) atroglaucum (Strand, 1913) is redescribed, L. (D.) ellipticeps, L. (D.) problematicum (Blüthgen, 1923), L. (D.) virideglaucum, and L. (D.) viridellum are supplementary described. A key to species is provided. Bionomical data, such as flight and flower records or habitat, are reported for some species. The distributions of all species are mapped. DNA barcodes of L. (D.) miyabei, L. (D.) pseudannulipes (Blüthgen, 1925), and L. (D.) virideglaucum are provided